(untitled) (Research, Society and Development, 2022)
The objective was to describe hospitalizations for pesticides recorded at a toxicological information and assistance center in the Northwest of Paraná, through a cross-sectional and retrospective study, with data from the List of Inpatients, from the Poison Control Center of the Regional University Hospital of Maringá. 170 individuals hospitalized with acute or chronic poisoning by pesticides were identified from January 2016 to December 2020. The age group from 15 to 45 years predominated - 117 cases (68.8%), however, 22 cases of children (12.9%) and 13 in the elderly (7.6%). Males represented 104 cases (61.2%). The suicide attempt occurred in 120 cases (70.6%) and the individual accident in 41 (24.1%). Pesticides of the herbicide toxicological class represented 59 cases (35%), followed by pyrethroid insecticides - 35 (21%) and organophosphates - 25 (15%), but no toxic agents were reported in 16 cases (9%). The mean hospital stay was 2.95% days and five cases (2.9%) were admitted to the intensive care unit. The death rate for the total number of cases was 3.5%, the majority by suicide. The data highlight the need to develop preventive strategies to deal with pesticide poisoning and the development of interventions to reduce the number of hospitalizations, minimizing complications and deaths.